The Poison Culture: The Forbidden Tradition, Social Class and Belief of Poisoned People in Aceh - Pohan, Zulfikar Riza Hariz (Universitas Islam Negeri Sunan Kalijaga, 2023)
The poison in Aceh (especially in Aceh Singkil) is called Aji. Aji is a mystical tradition aiming to achieve a certain spiritual level (maqam). There are some people referred to as Pekhaji (poison makers), whom the local people are wary of. And there are certain villages forbidden for foreigners because there is fear that the poison is added to food and drink. Even if a person is accused of being a Pekhaji or a village, it is considered forbidden, and no legal action is taken because it is based only on speculation. Aji as a spiritual practice is considered taboo; the Pekhaji's and forbidden villages are socially and economically marginalized. The forbidden villages and the Pekhaji are usually aimed at the poor and disadvantaged traditional village heads; the people accused as Pekhaji are poor people who do not get proper civil rights. This research examined rituals in the Aji tradition as part of social construction and analyzed religious studies by viewing social stratification in traditional villages and local rituals. The data in this research were collected through interviews and phenomenological field observations to explain all aspects of the Aji tradition in Aceh Singkil.